A methodological framework for measuring the level of convenience of transport ticketing systems - Zalar, Dušan; Ušpalytė-Vitkūnienė, Rasa; Rebolj, Danijel; Lep, Marjan (Transport, 2018)
Public transport sustainability is becoming a major driver for public transport development. Public transport ridership represents one of the key performance indicators of sustainability in the sense of balancing the economic, social and environmental aspects of public transport. There are various methods for improving the attractiveness of public transport for passengers by reducing resistances, which discourage potential and existing passengers to use public transport. Transport ticketing is one of the methods. This article presents a methodological framework for evaluating transport ticketing technologies with the use of a transport ticketing convenience model developed by the authors as well as some survey results through the application of the developed framework on traditional smart ticketing and contactless payment card ticketing technologies. First, a methodological framework for modelling ticketing convenience based on end-to-end passenger experience is presented. Second, a ticketing convenience model for barrier-free and double-sided validation baseline ticketing systems is developed. Third, the ticketing system based on contactless bank payment cards is compared with traditional smart ticketing systems in terms of convenience. It is shown that a contactless payment cards ticketing system has greater convenience or a better, more seamless travel experience than traditional smart systems. Finally, some research perspectives on enhancing the ticketing convenience model by using mobile smartphones with NFC, BLE and GPS technology, as well as the inclusion of technologies related to ticketing such as passenger information systems into the model, are contemplated.First Published Online: 3 May 2017